Entrepreneurship and the liberal arts : the making of Ashoka University - Sud, Mukesh, (SAGE Business. Cases., 2019)
In 2006, four entrepreneurs Vineet Gupta, Ashish Dhawan, Pramath Sinha and Sanjeev Bhikchandani decided to enter the higher education space in India. Their aim was to establish a world-class university that would prepare students for the new workplace. At the time, Indian universities had an outdated curriculum, uninspiring pedagogy and except for a few notable exceptions, largely failed to prepare graduates for the real world.